Teaching how to read the mind: the design of an edugame for the development of social skills in students with Autism Spectrum Disorders - Aiello, Paola; Di Tore, Stefano; Pace, Erika Marie; Sibilio, Maurizio (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
This paper presents a research aimed at creating an edugame whose objective is that of supporting inclusive teaching practices in the presence of students with Autism Spectrum Disorders. Taking into consideration the literature supporting the added value of technology to promote inclusive practices, the experimented edugame was designed in line with the phases envisaged in Howlin’s educational program. Such resources aid teachers to put into practice more sustainable individualized and differentiated instruction to respond to the students’ specific cognitive styles in Italian school contexts. The initial results from the testing of the edugame have demonstrated a greater appeal than the classic ‘paper and pencil’ test and an increase in the recognition of emotions and expressions.